QS. Al-Maidah Verse 8: A Reflection on Prophetic Justice - Ainun Murziq; Andri Nirwana AN (Universitas Muhammadiyah Surakarta, 2025)
This research aims to examine the application of the principle of justice contained in QS. Al-Maidah verse 8 within the social and political context of modern society. This verse teaches that every individual must be treated justly, without discrimination based on social background, religion, race, or other statuses. Although the concept of justice in this verse is universal and inclusive, its implementation in social reality is often hampered by structural inequalities, particularly in economic, political, and social sectors. This study employs a qualitative approach with a literature study method to analyze the exegesis of QS. Al-Maidah verse 8 and compare it to existing social conditions, especially in Indonesia. The results show that although various countries have proclaimed social justice policies, structural inequalities remain widespread, potentially creating discrimination and imbalances across various sectors of life. Justice in Islam, as depicted in QS. Al-Maidah verse 8, requires respect for the fundamental rights of every individual and equal opportunities in all aspects of life. Therefore, this study suggests the need for reforms in public policy to be more inclusive and focused on equalizing opportunities for all individuals, as well as emphasizing the importance of a paradigm shift in society to better appreciate diversity as a strength that can drive the realization of true justice.